2021
DOI: 10.2478/mdke-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-Top Television Services and Changes in Consumer Viewing Patterns in South Africa

Abstract: A significant change in consumer viewing habits has taken place globally with the introduction and growth of over-the-top television services (OTT TV). In the absence of scientific evidence on television consumer behavior viewership changes, this paper’s objective was to ascertain the television viewing patterns, given the rise of OTT TV services in South Africa. The study adopted a quantitative research approach using a convenience sampling method. Online survey questionnaires were distributed on reputable so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Studies, including Moghaddam, Car, Burgess, Mathur, Huang, Feamster, Felten, Mittal, and Narayanan (2019) have shown that the number of over-the-top television subscribers is on the drastic increase every day globally. Tengeh and Udoakpan (2021), also agreed with some researchers that such a spike has been a result of availability, accessibility, and low-cost broadband data existing globally. Park and Kwon (2019) pointed out that over-the-top media firms are transforming the competitive relationship among media firms in the broadcasting market and the structure of the broadcasting industry, hence, increasing accessibility, improving content delivery, and improving customer satisfaction through competition.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Studies, including Moghaddam, Car, Burgess, Mathur, Huang, Feamster, Felten, Mittal, and Narayanan (2019) have shown that the number of over-the-top television subscribers is on the drastic increase every day globally. Tengeh and Udoakpan (2021), also agreed with some researchers that such a spike has been a result of availability, accessibility, and low-cost broadband data existing globally. Park and Kwon (2019) pointed out that over-the-top media firms are transforming the competitive relationship among media firms in the broadcasting market and the structure of the broadcasting industry, hence, increasing accessibility, improving content delivery, and improving customer satisfaction through competition.…”
Section: Introductionsupporting
confidence: 52%
“…Similarly, Luthra (2021) in examining the influence of COVID-19 pandemic on subscription to OTT platforms found that respondents are favourably disposed to OTT platform and are willing to spend more in exchange for carefully crafted content. According to Tengeh and Udoakpan (2021), the access of viewers to Internet and linked devices has changed television consumption practices in South Africa giving preference to online streaming over traditional television. Ekwuazi (2014) found that the preference for DStv channels was based on tribe i.e.…”
Section: Review Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation